PENGARUH PENGGUNAAN TAS PENYIMPANAN OBAT TERHADAP KONTROL TEKANAN DARAH PASIEN HIPERTENSI - Niken Larasati; Sugiyono Sugiyono (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2022)
Number of people with hypertension in Indonesia is increasing. In addition, not all patients diagnosed with hypertension are adherent to treatment. Based on the 2018 Basic Health Research data, Yogyakarta was ranked second as the province with the highest hypertension patients in Indonesia. The purpose of this study is to determine the effect of using a medicine storage bag on blood pressure control of hypertension patients. This study used a pretest and posttest design with a control group of 36 patients’ sample at the Puskesmas Gamping 1 Yogyakarta from March to August 2019. At the beginning of the study, blood pressure data of patients in both groups were taken. The intervention group was given counseling to patients with medicine storage bags. Observations were made on the results of therapy in the form of controlled blood pressure attainment. The intervention resulted in a p-value of 0.031 for systolic and 0,000 for diastolic (p-value <0.05) indicated that there was an effect of using a medicine storage bag on the control of systolic and diastolic blood pressure in hypertensive patients. This study might conclude that medication aids are useful for hypertensive patients because they can increase the achievement of therapeutic targets.